The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4328/jcam.1690
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Suture Techniques

Abstract: ÖzetAmaç: Travmalar acil servise sık başvuru nedenlerindendir. Sütür, skalp kesisi olan hastaların tedavisinde sıklıkla gereklidir. Bu çalışmada skalp kesisi olan hastalarda farklı sütür tekniklerinin yara iyileşmesi, hasta memnuniyeti ve maliyet üzerine etkisinin araştırılması amaçlanmıştır. Gereç ve Yöntem:Çalışmaya toplam 60 hasta alındı. Hastalar geleneksel sütür (Grup 1), stapler (Grup 2) ve doku yapıştırıcı grubu (Grup 3) olarak üç gruba ayrıldı. Grupların karşılaştırılmasında χ 2 ve Kruskal-Wallis testl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…3 The use of staplers in closing scalp wounds has more advantages than the use of simple interrupted sutures in regard to patient satisfaction, wound healing, and concerning cost. 5 However, in our study, only 5.20% of the participants chose staplers when treating scalp wounds, while 77.90% opted for the simple interrupted technique despite it not being considered the best method of treating scalp wounds according to previous studies. 6 Moreover, many different suturing materials can be used on a wide variety of wound types, apart from the most suitable types of material.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…3 The use of staplers in closing scalp wounds has more advantages than the use of simple interrupted sutures in regard to patient satisfaction, wound healing, and concerning cost. 5 However, in our study, only 5.20% of the participants chose staplers when treating scalp wounds, while 77.90% opted for the simple interrupted technique despite it not being considered the best method of treating scalp wounds according to previous studies. 6 Moreover, many different suturing materials can be used on a wide variety of wound types, apart from the most suitable types of material.…”
Section: Discussionmentioning
confidence: 54%
“…One such study investigated a variety of techniques in relation to patient satisfaction, wound healing, and treatment cost in patients with a scalp laceration, finding that there are many alternatives (e.g., adhesions and staples) that have more advantages than simple suturing. 5,6 Other studies showed that cosmetic pleasing and patient satisfaction (which tend to be significantly heightened in horizontal wounds and running subcuticular suture techniques in contrast with the traditional simple interrupted method) are considered essential factors that assess the effect of the suture technique. [7][8][9] Another randomized controlled trial reviewed subcuticular versus interrupted skin suturing, comparing the superficial incisional surgical site infection rate after cesarean section (CS) in obese women.…”
Section: Introductionmentioning
confidence: 99%